2014
DOI: 10.4236/ojanes.2014.411041
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Volume Monitoring to Assess the Effect of Airway Maneuvers on Ventilation during Upper Endoscopy

Abstract: Introduction: Propofol use during endoscopic procedures has become increasingly popular and assessing and maintaining airway patency is a significant challenge. Anesthesiologists often use airway maneuvers to maintain airway patency and ventilation during procedural sedation. A novel, non-invasive, Respiratory Volume Monitor (RVM) that provided continuous, real-time measurements of minute ventilation (MV), tidal volume (TV) and respiratory rate (RR) was used to monitor respiratory performance before, during, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Furthermore, Holley et al demonstrated the superiority of MV moniting over monitoring RR alone during procedural sedation for upper endoscopic procedures [ 33 ]. During these procedures, the RVM detected decreases in MV in response to sedatives and also identified increases in MV following airway maneuvers such as chin lifts and jaw thrusts [ 34 , 35 ]. In addition to changes in MV, the RVM is also able to detect periods of airway obstruction [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Holley et al demonstrated the superiority of MV moniting over monitoring RR alone during procedural sedation for upper endoscopic procedures [ 33 ]. During these procedures, the RVM detected decreases in MV in response to sedatives and also identified increases in MV following airway maneuvers such as chin lifts and jaw thrusts [ 34 , 35 ]. In addition to changes in MV, the RVM is also able to detect periods of airway obstruction [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the group allocation, the patients in four groups were respectively sedated using propofol 1.5 mg/kg and sufentanil 0.1 μg/kg (group S), propofol 1.5 mg/kg and esketamine 0.2 mg/kg (group E0.2), propofol 1.5 mg/kg and esketamine 0.3 mg/kg (group E0.3), and propofol 1.5 mg/kg and esketamine 0.4 mg/kg (group E0.4). The dosage of propofol and sufentanil was determined according to the Chinese endoscopic guideline 16 and previous studies 17–19 . Esketamine or sulfentanil were prepared according to bodyweight and diluted with normal saline into a 10 mL syringe, then given to the patient 2 min before propofol.…”
Section: Methodsmentioning
confidence: 99%
“…The dosage of propofol and sufentanil was determined according to the Chinese endoscopic guideline 16 and previous studies. [17][18][19] Esketamine or sulfentanil were prepared according to bodyweight and diluted with normal saline into a 10 mL syringe, then given to the patient 2 min before propofol. Additional propofol 0.5 mg/kg was added to keep patients within target sedation level.…”
Section: Monitoring Of Patients and Anesthetic Proceduresmentioning
confidence: 99%